Frederick Street, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of Frederick Street. A policeman can be seen standing on the corner. The postcard is addressed to Pearl Fraze of Indiana, United States. Affixed to the postcard is a one penny postage stamp.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Streets--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; 1912; Architecture--Trinidad and Tobago; Wrought iron--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Police--Trinidad and Tobago; Frederick Street (Port of Spain)